جماليات التناص واستراتيجياته في المقامة الباقوزية لمحمود عياشي - حسان, أسماء; مرزوقي, عائشة; مالك, فضيلة (University of Eloued جامعة الوادي, 2024)
- احتلت المقامات مكانة مرموقة في الأدب العربي القديم منذ ظهورها، وكان رائدها هو بديع الزمان الهمذاني (ت398)، وصولا إلى الحفيد محمود عياشي الذي عالج قضايا عصره ومشاكل محيطة من خلالها، مهتما باللغة المتينة التي تحمل الجمال والمتعة والمعاني البعيده المرمى. - وعنيت دراستنا بموضوع ذا أهمية وجدير بالبحث وهو جماليات التناص واستراتيجياته في المقامة الباقوزية لمحمود عياشي، وتمثلت إشكالية الموضوع في ما يلي: كيف تجلت جماليات التضافر النص في (المقامة الباقوزية) وما جدوى الاشتغال عليه عبر هذا اللون الأدبي الساخر?، و حيث تضمنت الدراسة : - مدخل مفاهيمي، وقفنا فيه على أهم مفاهيم الدراسة وأبعادها وفصل نظري، تناولنا فيه إستراتيجية التناص و مستوياته ومصادره. "The Maqamat" had a prominent place in ancient Arabic literature since its appearance, and its pioneer was Badi al-Zaman al-Hamdhani (d. 398), up to the grandson Mahmoud Ayashi, who dealt with the issues of his time and surrounding problems through them, interested in the strong language that carries beauty, pleasure, and far meanings. Our study focused on a topic of importance and worthy of research, which is the aesthetics of intertextuality and its strategies in the Baquzian Maqamat by Mahmoud Ayashi. The problem of the topic was represented in the following How were the aesthetics of textual cohesion revealed in “The Baquzian Maqama” and what is the benefit of working on it through this satirical literary style? The study included A conceptual introduction, in which we discussed the most important concepts and dimensions of the study, and a theoretical chapter, in which we discussed the strategy of intertextuality, its levels, and sources.
أدب حديث ومعاصر
Keywords: إستراتيجية التناص ، المقامة الباقوزية، التناص الداخلي، التناص الخارجي